Development of anexpress-method for influence and genotyping of H1N1 and H7N9 virus avian influenza a strains by PCR-RFLP analysis - Buriachenko, Semen; Stegniy, Borys (ScienceRise: Biological Science, 2019)
Epizootic monitoring in recent years suggests that the highly pathogenic avian influenza A virus (H1N1) and (H7N9) actively circulate in the Eurasian countries. By 2016 - 2019 1.6 thousand outbreaks were recorded. For 2016 - 2019, 1.6 thousand cases of outbreaks were recorded. Of these, there are 872 cases in Europe. The monitoring of infected birds, both migratory and poultry, in places of cross-contact in Ukraine is relevant for preventing outbreaks of epizooties. The aim of the study. To develop an express method for the identification and determination of bird flu virus A H1N1 and H7N9 strains, based on a polymerase chain reaction with analysis of restriction fragment length polymorphism (PCR-RFLP) of the virus RNA. Results and discussion. The in silico analysis of the HA, NA, and NP gene amplicons allowed in silico to calculate the primers to the variable loci of the investigated genes, to calculate the reaction conditions, to determine restriction sites for the restriction enzyme to obtain theoretical PCR electrophoregrams. An express method for the detection and identification of influenza A H1N1 and H7N9 virus by three genes (HA, NA, and NP) of H1N1 and H7N9 RNA in polymerase chain reaction, combined with RFLP analysis, was developed. The method of rapid diagnostics is able to detect avian influenza virus A H1N1 and H7N9 and differentiate it from samples of other pathogens of viral infections of birds and animals. It was established, that the PCR-RFLP rapid diagnostic method is able to detect influenza A virus RNA of H1N1 and H7N9 strains with high sensitivity (100 % sensitivity). Conclusions.The developed method of PCR-based rapid identification, combined with RFLP analysis, makes it possible to significantly simplify the method of identification due to specific amplification of an RNA region having a polymorphic restriction site. Testing of this locus is possible by pre-PCR and restriction of the amplified fragment. The method of express - diagnosis of PLR-RFLP has been established for detecting RNA virus influenza A of high pathogenic H1N1 and H7N9 strains with high indicators of sensitivity (100 % sensitivity)